The Progressive Education Concept in the Perspective of K.H Ahmad Dahlan and Its Relevance with Islamic Education in the Industrial Revolution Era 4.0 - Algifari, Iqbal (JOIES (Journal of Islamic Education Studies), 2024)
This research is conducted based upon the anxiety and uncertainty in providing an applicable concept of Islamic education to the demands of the times, but on the one hand it is still trying to maintain Islamic values. The progressive education aims to provide a new paradigm, i.e. education that is in line with the trends required in the industrial revolution era 4.0 where human life coexists directly with advanced technology. This library research used a qualitative descriptive approach. The results of the research showed that first, the concept of progressive education from the perspective of K.H Ahmad Dahlan emerged as an answer to social issues. K.H Ahmad Dahlan that tended to be religious-rational, provided an overview of the foundations of progressive education, including intelligence, experience, and progress. Second, the characteristics of Islamic education in the industrial revolution era 4.0 lie in flexibility and digitalization to generate real personalities of Muslim. Third, the relevance of the concept of progressive education to Islamic education in industrial revolution era 4.0 lies in the same spirit in raising the modernization of education, as seen from the components of education, those are objectives, curriculum, educators and students, methods, and evaluation.